2011
DOI: 10.1039/c1np00051a
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeting by curcumin as revealed by molecular interaction studies

Abstract: Curcumin (diferuloylmethane), the active ingredient in turmeric (Curcuma longa), is a highly pleiotropic molecule with anti-inflammatory, anti-oxidant, chemopreventive, chemosensitization, and radiosensitization activities. The pleiotropic activities attributed to curcumin come from its complex molecular structure and chemistry, as well as its ability to influence multiple signaling molecules. Curcumin has been shown to bind by multiple forces directly to numerous signaling molecules, such as inflammatory mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
354
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 561 publications
(374 citation statements)
references
References 156 publications
11
354
0
9
Order By: Relevance
“…The affinity of this phytochemical for macromolecules in SVF (pH4.5) was therefore quantified and profound affinity of curcumin for glycoproteins and albumin was demonstrated (Fig. 3, the results of equilibrium dialysis), with slightly higher affinity for glycoproteins than for albumins as corroborated in other published articles (42). Interactions between curcumin and vaginal mucus could thus additionally reduce curcumin accessibility to systemic circulation via vaginal mucosa.…”
Section: Discussionsupporting
confidence: 56%
“…The affinity of this phytochemical for macromolecules in SVF (pH4.5) was therefore quantified and profound affinity of curcumin for glycoproteins and albumin was demonstrated (Fig. 3, the results of equilibrium dialysis), with slightly higher affinity for glycoproteins than for albumins as corroborated in other published articles (42). Interactions between curcumin and vaginal mucus could thus additionally reduce curcumin accessibility to systemic circulation via vaginal mucosa.…”
Section: Discussionsupporting
confidence: 56%
“…However, as the basal and HIF1A-independent release of VEGFA was also suppressed by curcumin, it is evident that other mechanisms involved in VEGFA production were also affected. It is known that curcumin has multiple targets and therefore interferes with multiple second messenger systems, intracellular signalling pathways and transcription factors (Kunnumakkara et al 2008, Gupta et al 2011, some of which are involved in the stimulatory action of different growth factors and neuropeptides on VEGFA secretion in pituitary adenomas (Renner et al 2004). For instance, it has been shown that TGF-B-induced VEGFA production, a process that is also critically involved in pituitary tumour development (Renner et al 2002), was significantly blocked by curcumin in human HT-1080 fibrosarcoma cells (Shih & Claffey 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has also been shown to inactivate TNF-␣ by direct binding. 76 In one study, curcumin docked at the receptor-binding sites of TNF-␣ and exhibited direct interaction by both noncovalent and covalent interactions. 77 Curcumin is currently in clinical trials for all those diseases for which TNF blockers have been approved.…”
Section: Tnf-␣ and The Golden Spicementioning
confidence: 99%